2006
DOI: 10.1111/j.1471-0528.2006.00930.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of a decision‐aid leaflet to facilitate women’s choice between pregnancy termination methods

Abstract: Objective To evaluate the effectiveness of a decision aid to help women choose between surgical and medical methods of pregnancy termination.Design A randomised controlled trial comparing a decision-aid leaflet about termination methods with a control leaflet about contraception.Setting An NHS regional centre for pregnancy termination.Sample All women less than 9 weeks of gestation referred for termination of pregnancy over 7 months in 2002.Methods Participants were given an envelope containing either the deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 27 publications
1
43
0
Order By: Relevance
“…There is evidence to suggest that some simple interventions can be included within a choice task to encourage individuals to adopt a more systematic approach to the evaluation of information [14,15]. This may lead to the formation of more stable preferences which are essentially closer to the underlying compensatory preferences assumed by economists in the analysis of DCE data.…”
Section: Introductionmentioning
confidence: 93%
“…There is evidence to suggest that some simple interventions can be included within a choice task to encourage individuals to adopt a more systematic approach to the evaluation of information [14,15]. This may lead to the formation of more stable preferences which are essentially closer to the underlying compensatory preferences assumed by economists in the analysis of DCE data.…”
Section: Introductionmentioning
confidence: 93%
“…The decision analytic method, and its direct application, the decision tree [31], have been widely used in designing DSTs for the last 10 years and was first applied to patient counselling in 1979 [32]. This method consists of assigning a cost and a probability of [110,111], 2003 Menorrhagia treatment Booklet Whelan [112], 2003 Breast cancer chemotherapy Decision board + booklet Whelan [113], 2004 Breast cancer surgery Decision board Wolf [114,115], 1996 PSA screening Script Wolf [116], 2000 Colon cancer screening Script Wong [117], 2006 Pregnancy termination Leaflet occurrence to each outcome and to combine them in order to generate the expected cost of each course of action. In the context of DST development, patients are asked to specify the utility of each available health option on a numerical scale.…”
Section: Prevalence Of ''Atheoretical'' Dstsmentioning
confidence: 99%
“…The evidence is lacking on the range of techniques that enable people to evaluate the information out there with their existing beliefs and/ or whether explicit techniques to enable trade-offs are needed for all decision aids in all contexts [49,50,73,101,103]. We have found that for less difficult decisions (choosing between treatments such as surgical or medical methods of termination of pregnancy), a simpler decision aid was sufficient to encourage more effective reasoning, less decisional conflict and an increased stability in attitudes over time [98]. However, for more difficult decisions (choosing to have or not have a treatment such as prenatal diagnosis), a more complex trade-off technique was required to achieve the same results [96].…”
Section: The Purpose Of Decision Aidsmentioning
confidence: 88%
“…Further, it is possible that such an intervention may be judged as a good patient decision aid because it adhered to the IPDAS checklist even though it was ineffective in facilitating patient decision making. Finally, there are interventions enabling effective patient decision making that do not include all the criteria identified within the IPDAS checklist [1,98,10]. If checklist adherence is used as a judgment about patient decision aid quality, effective patient decision aids could be unjustly rated as poor quality.…”
Section: The Different Purposes Of Patient Decision Aidsmentioning
confidence: 97%
See 1 more Smart Citation